Pengaruh Word of Mouth dan Brand Image terhadap Minat Konsumen di Elfast English Course Kampung Inggris Pare - Kenza Bisri Hariris; Ni Made Ida Pratiwi; Awin Mulyati (Politeknik Kampar, 2025)
This study aims to analyze the effect of Word of Mouth (WOM) and Brand Image on Consumer Interest In choosing Elfast English Course as a place to study. The study used a quantitative approach with data collection through an online questionnaire in the form of a google form distributed to Elfast English Course consumers. The sample was randomly selected using simple random sampling technique, and the data was analyzed using multiple linear regression with the help of SPSS version 27. The results showed that both Word of Mouth and Brand Image had a significant effect, both simultaneously and partially, on Consumer Interest. The coefficient of determination (R²) indicates that both variables are able to explain most of the variation in consumer interest. These findings provide insight for Elfast English Course management to continue to improve service quality and strengthen Brand Image. In addition, maximizing Word of Mouth strategies can be an effective way to attract new potential participants through satisfied customer recommendations.